The multifaceted roles of antibiotics and antibiotic resistance in nature - Sengupta, Saswati; Chattopadhyay, Madhab K.; Grossart, Hans-Peter (Frontiers in Microbiology, 2013)
Antibiotics are chemotherapeutic agents, which have been a very powerful tool in the clinical management of bacterial diseases since the 1940s. However, benefits offered by these magic bullets have been substantially lost in subsequent days following the widespread emergence and dissemination of antibiotic resistant strains. While it is obvious that excessive and imprudent use of antibiotics significantly contributes to the emergence of resistant strains, antibiotic-resistance is also observed in natural bacteria of remote places unlikely to be impacted by human intervention. Both antibiotic biosynthetic genes and resistance-conferring genes have been known to evolve billions of years ago, long before clinical use of antibiotics. Hence it appears that antibiotics and antibiotics resistance determinants have some other roles in nature, which often elude our attention because of overemphasis on the therapeutic importance of antibiotics and the crisis imposed by the antibiotic-resistance in pathogens. In the natural milieu, antibiotics are often found to be present in subinhibitory concentrations acting as signalling molecules supporting quorum sensing and biofilm formation. They also play an important role in the production of virulence factors and influence host-parasite interactions (e.g., phagocytosis, adherence to the target cell and so on). The evolutionary and ecological aspects of antibiotics and antibiotic-resistance in the naturally occurring microbial community are little understood. Therefore, the actual role of antibiotics in nature warrants in-depth investigations. Studies on such an intriguing behaviour of the microorganisms promise insight into the intricacies of the microbial physiology and are likely to provide some lead in controlling the emergence and subsequent dissemination of antibiotic resistance. This article highlights some of the recent findings on the role of antibiotics and genes that confer resistance to antibiotics in nature.